1, 3-Dipolar cycloadditions of nonstabilized azomethine ylides to planar chalcones via regio- and stereoselective route: A three-component strategy. Issue 4 (16th February 2016) - Gayen, Biswajit; Banerji, Avijit; Dhara, Kaliprasanna
ABSTRACT: Simple and efficient strategies toward the synthesis of trisubstituted pyrrolizidines and disubstituted oxazolidine systems by 1, 3-dipolar cycloaddition reactions using arylaldehydes andα -amino acids have been developed, followed by a one-pot, three-component strategy. Electron-deficient dipolarophiles, chalcones, were reacted with nonstabilized azomethine ylides derived from arylaldehyde and L-proline in dry dimethyl formamide, leading to substituted pyrrolizidines. The route to substituted oxazolidines involved cycloaddition to the C˭O bond of a second molecule of the aldehyde. The structures and stereochemistry of the cycloadducts were established by infrared (IR), NMR spectroscopy, and single-crystal x-ray crystallographic analyses. Condensed Fukui functions and local electrophilicity indices have been computed to characterize the reactive sites and predict the preferred interactions of azomethine ylides to planar chalcones. The softness-matching indices have been evaluated to determine the regioselectivity of the cycloaddition reactions. The theoretical predictions were found to be in complete agreement with the experimental results, implying that the density functional theory (DFT)-based reactivity indices correctly predict the regioselectivities of 1, 3-dipolar cycloadditions of azomethine ylides to planar chalcones. The frontier molecular orbital (FMO) energies, electronic chemical potentials, chemical hardness, chemical softness, and global electrophilicity indices of azomethine ylides have been calculated at the DFT/B3LYP/6-31 + G (d, p) level of theory. GRAPHICAL ABSTRACT: